The Evaluation of Ochratoxin A in Patients Suffer from Renal Failure - Haider Abbas Hadi Al-Mhanaa1 , Atheer B. Al-Obaidi 2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The study is conducted on 94 patients (54 male and 40 female) and 15 healthy people (10 male and 5 female) as the control group. All these cases were suffers from renal failure ,when attended to AL-Sader hospital in AL-Najaf province from February till May 2019. we make qualitative diagnosis by using TLC (thin layer chromatography) 29 cases have an ochratoxin A in serum and 65 cases without ochratoxin A and quantitative diagnosis by using HPLC (high-performance liquid chromatography ) for 25 cases from positive results (15 male and 10 female)and detects of WBCs count for 29 cases with ochratoxin A and 15 with out ochratoxin A .